2022
DOI: 10.1029/2022gb007391
|View full text |Cite
|
Sign up to set email alerts
|

Lithogenic Particle Flux to the Subantarctic Southern Ocean: A Multi‐Tracer Estimate Using Sediment Trap Samples

Abstract: Mineral dust is a key source of essential micronutrients, particularly iron (Fe), for phytoplankton in the Southern Ocean. However, observations of dust deposition over the Southern Ocean are sparse, hindering assessments of its influence on marine biogeochemistry. We present a time series (2010–2019) of lithogenic particle flux estimates using sediment trap samples collected at 1,000 m depth at the subantarctic Southern Ocean Time Series (SOTS) site. Lithogenic flux was estimated using individual Fe, aluminiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 145 publications
2
1
0
Order By: Relevance
“…The observations along SR3 demonstrated characteristic surface dFe depletion across the entire transect (Figure 3c). The mean dFe concentration across the entire transect in the surface 100 m was depleted to 0.14 ± 0.09 nmol/kg ( n = 54) (Figure 3c), indicating that surface external sources of dFe such as atmospheric deposition were minimal, as previously observed based on sinking particle concentrations (Traill et al., 2022). While surface waters (STCW, AASW and SAMW) were very low in dFe, localized sub‐surface regions (∼500 m depth) of high dFe concentrations (>1 nmol/kg) were observed adjacent to the Antarctic and Tasmanian continental shelves (Figure 3c).…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…The observations along SR3 demonstrated characteristic surface dFe depletion across the entire transect (Figure 3c). The mean dFe concentration across the entire transect in the surface 100 m was depleted to 0.14 ± 0.09 nmol/kg ( n = 54) (Figure 3c), indicating that surface external sources of dFe such as atmospheric deposition were minimal, as previously observed based on sinking particle concentrations (Traill et al., 2022). While surface waters (STCW, AASW and SAMW) were very low in dFe, localized sub‐surface regions (∼500 m depth) of high dFe concentrations (>1 nmol/kg) were observed adjacent to the Antarctic and Tasmanian continental shelves (Figure 3c).…”
Section: Resultssupporting
confidence: 77%
“…The observations along SR3 demonstrated characteristic surface dFe depletion across the entire transect (Figure 3c). The mean dFe concentration across the entire transect in the surface 100 m was depleted to 0.14 ± 0.09 nmol/kg (n = 54) (Figure 3c), indicating that surface external sources of dFe such as atmospheric deposition were minimal, as previously observed based on sinking particle concentrations (Traill et al, 2022).…”
Section: Distribution Of Dissolved and Particulate Iron Across Sr3supporting
confidence: 73%
See 1 more Smart Citation
“…Trace metal compositions in sinking particles retain valuable information to identify their sources and investigate the associated cycling processes. For example, it has been demonstrated that Al, Fe, Ti, and Th are useful indicators for mineral dust deposition [9]. In addition, Cu, Pb, Zn, and V are enriched in sediment trap samples relative to their crustal abundance in the North Pacific Western Subarctic Gyre and Sargasso Sea [10][11][12], suggesting that anthropogenic signals in trace metals can be captured by sinking particles.…”
Section: Introductionmentioning
confidence: 99%